Bounded risk estimation of the hazard rate function of the exponential distribution: Two-stage procedure. Issue 1 (2nd January 2017) - Mahmoudi, Eisa; Lalehzari, Reihaneh
ABSTRACT: In this article, we consider sequential point estimation of hazard rate function of an exponential distribution ( ) subject to the risk function given as, where 0< A <∞ and ω >0 are known constants. We provide explicit formulas for the distribution of the total sample size, N m, and of the expected value and risk of the estimator of the hazard rate function of the exponential distribution. In addition, we propose how to determine the parameter K ( = K ( m, A )) of the stopping variable N m so that the risk is uniformly bounded by ω . In the end, the performances of the proposed methodology are investigated with the help of simulations and two applied examples.